Auditor quality analysis of audit findings in Timor-Leste - Aris Astuti, Wati; Surtikanti, Surtikanti; Eneida, (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
This study aims to provide empirical evidence regarding the quality of auditors obtained from audit findings and the performance of local government apparatus in producing audit findings at the Central Government Inspectorate. The research method used is a descriptive verification method with SPSS 2.0. The results of the study show that auditor quality has a significant effect on audit findings. This proves that a qualified auditor in disclosing audit findings requires professional expertise and skills in carrying out his duties. And the results of research on audit findings have a poor performance impact on local government administration. This indicates that the fewer the number of audit findings found, the better the performance of local government administration. In other words, the fewer problems or violations found during the audit process, the better the performance of the local government.